BIOSYNTHESIS AND CHARACTERIZATION OF SILVER NANOPARTICLES FROM MARINE MACROSCOPIC RED SEAWEED HALYMENIA PORPHYROIDES BOERGESEN (CRYPTON) AND ITS ANTIFUNGAL EFFICACY AGAINST DERMATOPHYTIC AND NON-DERMATOPHYTIC FUNGI - MANAM, VISHNU KIRAN; SUBBAIAH, MURUGESAN (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Objective: The current study illustrates the biosynthesis of economically scalable and energy efficient colloidal silver nanoparticles (AgNPs) from marine red seaweed Halymenia porphyroides Boergesen (Crypton) collected from Southeast coast of Tamil Nadu, India, and their antifungal efficacy against dermatophytic and non-dermatophytic fungi was evaluated. Methods: The biosynthesis of silver nanoparticles from marine macroscopic red seaweed H. porphyroides Boergesen were synthesized by green synthesis method and characterized by UV–Vis spectroscopy, Fourier transform infrared (FT-IR) spectroscopy, X-ray diffraction, thermogravimetric analysis (TGA), scanning electron microscope (SEM), and transmission electron microscopy (TEM). The efficacy of silver nanoparticles against dermatophytic and non-dermatophytic fungi was performed by disk diffusion method. Results: The presence of silver nanoparticles with an average size between 34.3 and 80 nm and exhibiting face-centered cubic structure was confirmed. SEM revealed the morphology of the nanoparticles as spherical and TEM exhibited the nanoparticle distribution. The FT-IR spectra confirmed the presence of potential biomolecules in the seaweed crude extract which is responsible for reducing and capping the bioreduced silver nanoparticles. The UV absorption spectra at 430.5 nm revealed the characteristic spectra of the silver nanoparticles. The purity and the thermal stability of silver nanoparticles were revealed by TGA. Silver nanoparticles showed significant efficacy against dermatophytes and Rhizopus microsporus among non-dermatophytes. Conclusion: Intermediate efficacy was observed against dermatophytes and among non-dermatophytic fungi R. microsporus exhibited better efficacy, whereas Aspergillus flavus were resistant to the biosynthesized silver nanoparticle.